Association between economic performance and corporate sustainability index of São Paulo stock exchange (Gestão & Regionalidade, 2016)
The effect of companies' socio-environmental action on economic outcomes provokes a discussion of opposing views. Thereare those who claim that the adoption of socially responsible practices stimulates economic performance and, on the otherhand, there is the view that such practices are causing irrecoverable costs for companies. Given this discussion, this studyaims to test whether companies considered sustainable - listed in the Corporate Sustainability Index (ISE, in the Portugueseacronym) - provide superior financial returns compared to other companies in the São Paulo Stock Exchange (BM&FBOVESPA).The hypothetico-deductive method was used, and data analysis was made comparing the behavior of the stocks ofISE companies to the other stocks of BM&FBOVESPA, using a parametric test to compare means (t-test). The results showevidence of superiority of the ISE portfolio against other companies in the studied period.